Digital aplications for CPLDs - Dueck, Robert K.
Robert Dueck received his degree in Electrical Engineering from the University of Manitoba, in Winnipeg, Canada and worked for several years as a design engineer at Motorola Canada in Toronto. He began his teaching career in 1986, specializing in digital and microcomputer subjects in the Electronics and Computer Engineering Technology programs at Seneca College in Toronto. He now teaches digital design and related courses at Red River College in Winnipeg. Mr. Dueck is a member of the Association of Professional Engineers and Geoscientists of Manitoba (APEGM) and the Institute of Electrical and Electronics Engineers (IEEE).